Love at First Glance but Not After Deep Consideration: The Impact of Sexually Appealing Advertising on Product Preferences - Hu, Fengpei; Wu, Qingyuan; Li, Yiwei; Xu, Weijie; Zhao, Lei; Sun, Qingzhou (Frontiers in Neuroscience, 2020)
In advertising studies, the impact of sexually appealing advertisements (hereafter “ads”) on consumers’ product preferences is highly controversial. This paper explores (1) how such ads affect consumers’ product preferences at the gazing stage (initial stage of exposure to the ad) and evaluation stage (final product preference), and (2) which type of product (utilitarian vs. hedonic) is more suited to such ads. We used an electroencephalogram to record participants’ product preferences at the gazing stage and self-reported product preferences at the evaluation stage. The results indicated that participants preferred ads with high sex appeal at the gazing stage and ads with low sex appeal at the evaluation stage. Further, compared to utilitarian products, hedonic products were more suited to sexually appealing ads. The findings suggest that the effect of such ads on consumers’ product preferences varies depending on their cognitive stage and the type of product advertised.